Design of liposomal formulations for cell targeting - Nogueira, E. (2015)
Liposomes have gained extensive attention as carriers for a wide range of drugs due to being both nontoxic and biodegradable as they are composed of substances naturally occurring in biological membranes. Active targeting for cells has explored specific modification of the liposome surface by functionalizing it with specific targeting ligands in order to increase accumulation and intracellular uptake into target cells. None of the Food and Drug Administration-licensed liposomes or lipid nanoparticles are coated with ligands or target moieties to delivery for homing drugs to target tissues, cells or subcellular organelles. Targeted therapies (with or without controlled drug release) are an emerging and relevant research area. Despite of the numerous liposomes reviews published in the last decades, this area is in constant development. Updates urgently needed to integrate new advances in targeted liposomes research. This review highlights the evolution of liposomes from passive to active targeting and challenges in the development of targeted liposomes for specific therapies.